The positive impact of electronic healthcare integration on quality and safety: a systematic review - Abashidze-Gabaidze, Gulnara; Gakharia, Tamar; Jorbenadze, Maka; Loria, Lasha; Dzodzuashvili, Elene; Gabaidze, Mishiko; Grigalashvili, Levani (International Journal Of Community Medicine And Public Health, 2025)
In the modern world, the vast and ever-growing volume of medical knowledge has become so large that clinicians may not be able to process it effectively, contributing to medical errors and suboptimal care worldwide. At this time, the most effective way to improve global health is to focus on the implementation of e-health globally. The rapid evolution of e-health technologies presents a transformative opportunity to enhance healthcare delivery. This literature review aims to synthesize evidence on the positive impact of integrating e-health solutions on the quality and safety of patient care. The goal of our research is to examine the benefits and challenges of e-healthcare and make global recommendations for both Georgia and the healthcare system in general. The research methodology is a literature review with narrative synthesis; A comprehensive narrative review of scholarly articles published in English over the last 10 years (2015-2025) was conducted. Key databases were systematically searched using terms such as "e-health," "digital health," "telemedicine," "health information technology," "quality of care," "patient safety," and "healthcare outcomes." Inclusion criteria focused on studies evaluating the direct or indirect positive effects of e-health interventions on quality and safety metrics. The review reveals consistent evidence demonstrating that e-health integration significantly contributes to improved healthcare quality and safety. Specific positive impacts include enhanced diagnostic accuracy through remote consultations, reduced medication errors via electronic prescribing systems, increased patient engagement and adherence through digital health platforms, and more efficient care coordination facilitated by shared electronic health records (EHRs). Furthermore, e-health has been shown to improve access to care, particularly in remote areas, and to bolster surveillance and response capabilities during public health crises, thereby indirectly safeguarding population health. This further proves that the best way to develop global healthcare is to integrate e-health and develop appropriate programs globally. The findings underscore the critical role of e-health in fostering a safer and higher-quality healthcare environment. Strategic integration of these technologies can lead to tangible improvements in patient outcomes, operational efficiency, and overall system resilience. Future research should focus on optimizing implementation strategies and addressing potential disparities to maximize the benefits of e-health across diverse healthcare settings.